Standard method for evaluating the strength of brazed joints (American Welding Society, 2008)
Abstract: This standard describes the test methods used to obtain brazed strength data of the short-time testing of single-lap joints in shear, butt-tension, stress-rupture, creep-strength, four-point-bending, and ceramic-tensile-button-specimens. Specimen preparation methods, brazing procedures, testing techniques, and methods for data analysis are detailed. Sample forms for recording data are presented. A graphical method of data presentation relates shear stress to overlap distance.
"AWS C3.2M/C3.2:2008 an American National Standard."
"Supersedes AWS C3.2M/C3.2:2001."
"Approved by American National Standards Institute January 4, 2008."
"Reproduced by World Engineering Xchange with the permission of AWS under royalty agreement."
Keywords: Brazed joints -- Testing.; Braze welding -- Testing.; Brazing -- Testing.; elektronické knihy; electronic books